KETAHANAN PANGAN DUNIA SEBAGAI DAMPAK PERANG UKRAINA RUSIA BERDASARKAN HUKUM INTERNASIONAL - Nababan, Desvo Richat (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
In recent years, the war between Russia and Ukraine has had an impact on countries inthe world that are dependent on the conflicting countries in terms of food security which hascaused a food crisis which has caused world hunger rates to increase and created a situationof economic and political instability in the world. The right to food is a basic human rightrecognized in international, regional and national instruments. Therefore, the researchobjectives of this thesis are: first, to determine the impact of world food security as a result ofthe Ukraine-Russia war based on international law. Second, to find out the role of InternationalLaw in overcoming food security due to the impact of the Ukraine-Russia war.The type of research used by the author is normative legal research or what is known as